Influence of Ongoing Task Difficulty and Motivation Level on Children’s Prospective Memory in a Chinese Sample - Han, Pi-guo; Han, Lei; Bian, Yu-long; Tian, Yu; Xu, Min-xia; Gao, Feng-qiang (Frontiers in Psychology, 2017)
Prospective memory (PM) is the process associated with the task of realizing delayed intentions in the future. Researchers distinguish two types of PM, namely time-based PM (tbPM) and event-based PM (ebPM). Experiment 1 investigated the developmental trajectory of 3- to 5-year old preschool children’s PM ability, and the occurrence of delayed retrieval (children execute the PM task in a larger window of opportunity) in both tbPM and ebPM tasks. Results revealed that the 5-year-old children outperformed the 3- and 4-year-old children in PM. Moreover, delayed retrieval was more likely to occur in tbPM task than in ebPM task. In Experiment 2, the influence of ongoing task (OT) difficulty on PM performance was investigated with a sample of 5-year-old children. Results revealed no significant effect of OT difficulty on PM performance. In Experiment 3, we improved children’s motivation level to complete the OT, then explored the influence of OT difficulty on children’s PM performance. Results revealed that the effect of OT difficulty on PM performance became significant after increasing the children’s motivation to complete the OT. These results provide insights into the mechanism of attentional resource allocation in PM tasks and have crucial educational and social implications.